2021
DOI: 10.26434/chemrxiv.12917957.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Permeation Mechanism of Cisplatin through a Dioleoylphosphocholine Bilayer

Abstract: The investigation of the intermolecular interactions between platinum-based anticancer drugs and lipid bilayers is of special relevance to unveil the mechanisms involved in different steps of the anticancer mode of action of these drugs. We have simulated the permeation of cisplatin through a model membrane composed of 1,2-dioleoyl-sn-glycero-3-phosphocholine lipids by means of umbrella sampling classical molecular dynamics simulations. The initial physisorption of cisplatin into the polar region of the lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
13
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 27 publications
(26 reference statements)
3
13
3
Order By: Relevance
“…In regard with this classification, we observe that at the minimum of the free-energy profile the overall nonelectrostatic interactions amount to 18.1 kcal/mol, thus resulting to be repulsive, while the electrostatic contribution is -67.1 kcal/mol (Figure 3b). Therefore, the electrostatic interaction is the main component of the interaction energy; this result is in agreement with the EDA performed considering a classical force field, 30 although it should be emphasized that in the latter case the non-electrostatic component resulted to be attractive, unlike the quantum mechanical analysis performed in this work. Interestingly, when analyzing the averages of the electrostatic and the non-electrostatic components at the center of the membrane (Fig-…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In regard with this classification, we observe that at the minimum of the free-energy profile the overall nonelectrostatic interactions amount to 18.1 kcal/mol, thus resulting to be repulsive, while the electrostatic contribution is -67.1 kcal/mol (Figure 3b). Therefore, the electrostatic interaction is the main component of the interaction energy; this result is in agreement with the EDA performed considering a classical force field, 30 although it should be emphasized that in the latter case the non-electrostatic component resulted to be attractive, unlike the quantum mechanical analysis performed in this work. Interestingly, when analyzing the averages of the electrostatic and the non-electrostatic components at the center of the membrane (Fig-…”
supporting
confidence: 89%
“…in comparison with the decrease in the Pauli repulsion. Contrary to the classical result,30 the electrostatic component is predominant in both regions of the membrane, and the Pauli repulsive component plays a major role in determining the overall non-electrostatic component, suggesting that the repulsive component is underestimated by classical force fields.Finally, we have observed that when cisplatin is closer to the polar heads, the electrostatic and induction components display strong correlations with the distance between cisplatin and the choline moiety of DOPC, whereas the dispersion energy does not show a strong dependence on a particular distance. At the center of the membrane, when cisplatin is closest to the oleyl moieties, neither of the attractive components display correlations with particular groups.…”
contrasting
confidence: 78%
“…[21][22][23][24][25][26] Specifically, the passive diffusion of cisplatin through different lipid bilayers has been investigated by umbrella sampling simulations. [27][28][29][30] Despite the significant mechanistic details obtained from the previous theoretical work, the nature of the drug/lipid interactions has been barely characterized in terms of simple force field contributions. 30 However, a more realistic description requires the use of more accurate methodologies, such as quantum mechanical interaction energy partitioning schemes based on variational or perturbational approaches.…”
mentioning
confidence: 99%
“…[27][28][29][30] Despite the significant mechanistic details obtained from the previous theoretical work, the nature of the drug/lipid interactions has been barely characterized in terms of simple force field contributions. 30 However, a more realistic description requires the use of more accurate methodologies, such as quantum mechanical interaction energy partitioning schemes based on variational or perturbational approaches. [31][32][33][34] These methods provide different contributions to the total interaction energy, such as Pauli, electrostatic, induction and dispersion terms, some of them not properly described by neither fixed-charge nor polarizable force fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation